PROBLEMS AND SOLUTIONS IN TEACHING ICT AT MEDICAL UNIVERSITIES - Sayfullaeva Dilbar Izzatillaevna (Western European Studies, 2025)
The widespread implementation of information and communication technologies (ICT) has become a key aspect of the modernization of education, particularly in the field of medical sciences. This article examines the critical problems faced in the process of teaching ICT at medical universities. The study identifies several major challenges, including outdated technical infrastructure, the shortage of specialized teaching personnel with sufficient ICT competencies, the limited integration of digital tools into the curriculum, and the insufficient digital literacy skills of both students and faculty members. Special attention is given to organizational and methodological barriers that hinder the effective use of ICT in the educational process. In response to these challenges, the article proposes a set of practical solutions aimed at improving the quality of ICT education in medical universities. These include the modernization of technical resources, the development of targeted training programs for educators, the inclusion of ICT-focused modules into the medical curriculum, and the promotion of interdisciplinary approaches that combine medical knowledge with digital skills. Furthermore, the study highlights the need for continuous professional development and the creation of institutional strategies that foster a digital learning environment
Keywords: information and communication technologies; medical universities; teaching